Squaring bilateralism with multilateralism: What investment law reformers can learn from the international tax regime - Wolfgang Alschner (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2020)
The 2018 OECD Multilateral Instrument updates thousands of bilateral taxation treaties in substance and procedure. This sweeping reform of the tax regime offers valuable lessons to investment law reformers on how to square bilateralism with multilateralism, align older agreements with current best practices, and impose minimum standards while preserving flexibility.
Keywords: 330